Investigation of permanent magnet synchronous motor with various magnet configurations - Dong, Yafei (Nanyang Technological University, 2024)
The project aims to investigate the performance of several Permanent Magnet Synchronous Motor (PMSM) models with different configurations for Hybrid Electric Vehicle application. PMSM has become a hot research topic globally in recent decades as it is found to be an effective source for electric vehicles applications. This project mainly explored Surface Mounted PMSM and Halbach Array PMSM configurations. Each configuration was used to create an 8-pole, 12-slot motor and an 8-pole, 24-slot motor using the software JMAG-Designer. Total of 4 models were designed and simulated, the main comparing parameters for their overall performance were average torque, output power, efficiency and costs. The results showed that the 8-pole, 24-slot Surface Mounted PMSM has the best performance among the 4 designs which is more appropriate for Hybrid Electric Vehicle application.